Voluntarism and the fruits of collaboration: the IBM user group, Share. - Akera, Atsushi (Technology & Culture, 2001)
An overview of Share, a voluntary cooperative organization made up of customers of IBM (International Business Machines), is presented. Share developed early operating procedures, operating systems, and a body of knowledge that would become known as systems programming. It also provided early programmers with a forum for establishing their work as a new field of knowledge, a body of practice, and a nascent profession. The most important work of Share took place between 1955 and 1958.